2016
DOI: 10.1103/physrevd.94.054028
|View full text |Cite
|
Sign up to set email alerts
|

SuppressedBPVCPasymmetry:CPTconstraint

Abstract: Charge Parity asymmetry in charmless B meson decays is a key issue to be understood. Many theoretical calculations have been performed using short distance factorization approaches which, in general, do not take into account the CPT invariance constraint. For each channel with CP violation there is an equal amount of CP asymmetry in another channel or other channels, with an opposite sign. This happens if these channels are coupled through final state interactions (FSI). In the specific process B → P V , invol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This is because A CP in eq. (4.3) is only generated by a vector-scalar interference, which always comes with a cos θ π term, and hence the CP asymmetry always switches sign when comparing cos θ > 0 and cos θ < 0 (see also [35][36][37] for an elaborate discussion on these issues). However, if the CP asymmetry were dominated by two S or S-D wave interferences, the CP asymmetry would not switch sign, which could be an explanation for the behaviour in this region.…”
Section: Jhep10(2017)117mentioning
confidence: 99%
“…This is because A CP in eq. (4.3) is only generated by a vector-scalar interference, which always comes with a cos θ π term, and hence the CP asymmetry always switches sign when comparing cos θ > 0 and cos θ < 0 (see also [35][36][37] for an elaborate discussion on these issues). However, if the CP asymmetry were dominated by two S or S-D wave interferences, the CP asymmetry would not switch sign, which could be an explanation for the behaviour in this region.…”
Section: Jhep10(2017)117mentioning
confidence: 99%
“…Curiously, it should be noted that this dual theory is analogous to a superconducting vortex strings [10]. Mention should be made, at this point, to an equivalent condensed matter picture from the above studies, where the vortex lines play the role of magnetic monopoles [9].…”
mentioning
confidence: 92%
“…For instance, recently a topological field theory description of (1 + 3)-D topological superconductors has been discussed [8]. In this work, the topological superconductor is described through a topological coupling between the electromagnetic field and the superconducting phase fluctuation, in much the same way as the coupling of axions with an Abelian gauge field.Most recently, it has been shown that a compact Abelian Higgs model with a θ-term in (1 + 3)-D may be considered as an effective field theory for a topological Mott insulator [9]. Interestingly, it was also shown that this effective theory is dual to an axionic superconductor model [3], which contains both particle and vortex degrees of freedom.…”
mentioning
confidence: 99%
See 2 more Smart Citations